The effect of slicing jpeg file on the web page download time / Fakhrul Hazman Yusoff, Anita Mohd Yasin and Rozianawaty Osman - Yusoff, Fakhrul Hazman; Mohd Yasin, Anita; Osman, Rozianawaty (Universiti Teknologi MARA, Perlis, 2005)
Image compression plays a vital part in displaying image on the Internet. Image compression format such as JPEG makes the file smaller hence speed up the download time. This paper will evaluate the usage of slicing technique on JPEG-based image file. Experiments are conducted in establishing whether slicing technique do contribute to reduction in total file size and speed up the download of an image file. Based on the finding, it is concluded that image slicing can reduce image size in certain situation. On the other hand image slicing will not significantly reduce the download time. However, as pointed out by the research image slicing do play some important role in overall image display mechanism in a website to compensate its slightly slower download time.